1990
DOI: 10.1037/0022-006x.58.6.741
|View full text |Cite
|
Sign up to set email alerts
|

Social skills training with schizophrenics: A meta-analytic evaluation.

Abstract: A meta-analytic review of 27 studies on social skills training with schizophrenics was conducted to address 3 critical issues in the literature: (a) the magnitude of treatment effects relative to different outcome measures; (b) the extent of the generalization and maintenance of treatment effects; and (c) the impact of 2 methodological issues: diagnostic clarity and training variations. Social skills training has a strong, positive impact on behavioral measures of social skill, self-rated assertiveness, and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0
9

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(153 citation statements)
references
References 13 publications
4
137
0
9
Order By: Relevance
“…Fifteen of the studies reviewed included functioning measures and the average effect size for improvement in functioning ( d =0.38) and negative symptoms ( d =0.44) was comparable to that for positive symptoms ( d =0.37). Numerous studies of consumers with schizophrenia have also shown that SST improves functioning (10, 11). A meta-analysis of 22 SST trials (11) found a large effect size for proximal content-mastery outcomes ( d =1.20), moderate effect sizes for intermediate outcomes, including performance-based measures of social and daily living skills ( d =0.52), community functioning ( d =0.52), and negative symptoms ( d =0.40), and small effect sizes for more distal outcomes, like other symptoms ( d =0.15) and relapse ( d =0.23).…”
mentioning
confidence: 99%
“…Fifteen of the studies reviewed included functioning measures and the average effect size for improvement in functioning ( d =0.38) and negative symptoms ( d =0.44) was comparable to that for positive symptoms ( d =0.37). Numerous studies of consumers with schizophrenia have also shown that SST improves functioning (10, 11). A meta-analysis of 22 SST trials (11) found a large effect size for proximal content-mastery outcomes ( d =1.20), moderate effect sizes for intermediate outcomes, including performance-based measures of social and daily living skills ( d =0.52), community functioning ( d =0.52), and negative symptoms ( d =0.40), and small effect sizes for more distal outcomes, like other symptoms ( d =0.15) and relapse ( d =0.23).…”
mentioning
confidence: 99%
“…Lors d'une méta-analyse réalisée sur les 27 études considérées les plus valides, Benton et Schroeder (1990) concluent que l'entraînement aux habiletés permet l'apprentissage de comportements sociaux adaptatifs, en-traîne des apprentissages sociaux durables pouvant se généraliser et permet une sortie plus rapide de l'hôpital ainsi qu'une diminution des rechutes.…”
Section: Mmêêmêêêimêmmmmmmmêêmammêêmêiêêêiêêmmmrunclassified
“…Three meta-analyses of SST studies (Benton & Schroeder, 1990;Corrigan, 1991;Dilk & Bond, 1996) found strong evidence for effectiveness in improving social competence, suppressing symptoms and postponing relapse. A fourth (Pilling, Bebbington et al, 2002) found no evidence for any kind of effectiveness.…”
Section: Outcome Research Methodology and Evidence Basementioning
confidence: 99%